Circulação, consumo mundial de carne e obesidade: coincidências ou co-incidências? - Hervé Théry; Patrick Caron (Confins)
Consumption of meat, especially beef, is often questioned for its effects on human health, particularly because of the growing prevalence of obesity with which it is associated by some. To help see if these are coincidences or co-incidences, the article uses mapping resources, maps were produced from FAO and WHO FaoStat databases, using the Cartes et Données software (Articque) then an additional graphic processing on Adobe Illustrator